1997
DOI: 10.1002/(sici)1098-2396(199705)26:1<36::aid-syn4>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Combined phentermine/fenfluramine administration enhances depletion of serotonin from central terminal fields

Abstract: Administration of phentermine (Phen) together with (+/-) fenfluramine (Fen) enhances the weight reduction that is observed with either drug alone; consequently, these anorectic agents are commonly prescribed together for weight reduction. Repeated administration of Fen is known to cause long-term depletion of axonal serotonin (5-HT) and loss of 5-HT transporters, and is therefore considered neurotoxic. We now report that combined administration of Phen/Fen (5 mg/kg/3.125 mg/kg, and 20 mg/kg/3.125 mg/kg) can en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Fenßuramine has been at the center of a decade-long dispute over potential neurotoxicity. When combined with PHEN, there either may (Lew et al 1997) or may not (Baumann et al 1996) be a potentiation of these e¤ects. We reported (Roth and Rowland 1997) no loss of paroxetine binding sites in frontal cortex by combining a low dose of DFEN (2 mg / kg) with PHEN (5 mg / kg).…”
Section: Discussionmentioning
confidence: 99%
“…Fenßuramine has been at the center of a decade-long dispute over potential neurotoxicity. When combined with PHEN, there either may (Lew et al 1997) or may not (Baumann et al 1996) be a potentiation of these e¤ects. We reported (Roth and Rowland 1997) no loss of paroxetine binding sites in frontal cortex by combining a low dose of DFEN (2 mg / kg) with PHEN (5 mg / kg).…”
Section: Discussionmentioning
confidence: 99%
“…are comparable to those of MDMA and MDA (Appel et al, 1989;Harvey and McMaster, 1975;Molliver and Molliver, 1990;Sanders-Bush et aI., 1975;Zaczek et al, 1990) and the extent of neurotoxicity apparently is enhanced by phentermine (PHEN) (Lew et al, 1997), which is the combination in the diet drug known as FEN-PHEN. The d-isomer of FEN is more potent than the/-isomer (Kleven and Seiden, 1989).…”
Section: Methamphetaminementioning
confidence: 90%
“…The d-isomer of FEN is more potent than the/-isomer (Kleven and Seiden, 1989). However, when PHEN is administered to rats in a single day at a dosage producing anorexia, neurotoxicity apparently does not occur (Lew et al, 1997).…”
Section: Methamphetaminementioning
confidence: 99%
“…Animal studies clearly indicate a synergism between phentermine and dexfen¯uramine on the reduction of appetite and body weight in rats. 25,26 Animal studies have also demonstrated synergism between phentermine and fen¯ur-amine on reduction of brain serotonin levels, 51,52 and between dexfen¯uramine and phentermine on vasoconstriction of pulmonary arterial vessels. 39 Recent studies indicate the coadministration of phentermine increases the incidence of valve disease associated with fen¯uramine or dexfen¯uramine.…”
Section: Discussionmentioning
confidence: 99%